2017
DOI: 10.1074/jbc.m116.763946
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Process of Activation of Cancer-promoting Zinc-requiring Ectoenzymes by Zinc Metalation Mediated by ZNT Transporters

Abstract: Zinc-requiring ectoenzymes, including both secreted and membrane-bound enzymes, are considered to capture zinc in their active site for their activation in the early secretory pathway. This idea has been confirmed by our studies conducted using tissue-nonspecific alkaline phosphatase (TNAP), which is elaborately activated by means of a two-step mechanism by zinc transporter 5 (ZNT5)-ZNT6 heterodimers and ZNT7 homodimers, through protein stabilization followed by enzyme activation with zinc in the early secreto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Indeed, a similar upregulation of ZnT5, ZnT6, and ZnT7 were found in grade 4 glioma patients, compared with grade 2 patients. 30,31 Autotaxin, matrix metalloproteinase 9, and carbonic anhydrase IX require ZnT5-ZnT6 heterodimers and ZnT7 homodimers for their activation and secretion. ZnT5/ZnT6 heterodimer and ZnT7 homodimer carry Zn 2+ from the cytosol into the vesicles of early secretory pathway; once inside, the metal ion is used for metallation, activation, and secretion of specific zincdependent enzymes (ecto-enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a similar upregulation of ZnT5, ZnT6, and ZnT7 were found in grade 4 glioma patients, compared with grade 2 patients. 30,31 Autotaxin, matrix metalloproteinase 9, and carbonic anhydrase IX require ZnT5-ZnT6 heterodimers and ZnT7 homodimers for their activation and secretion. ZnT5/ZnT6 heterodimer and ZnT7 homodimer carry Zn 2+ from the cytosol into the vesicles of early secretory pathway; once inside, the metal ion is used for metallation, activation, and secretion of specific zincdependent enzymes (ecto-enzymes).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple protein sequence alignment was generated using ClustalW. To establish cells stably expressing WT or mutant ZNT2 and ZNT3 proteins, DNA was electroporated as described previously 60 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was performed as described previously 60 . Blotted polyvinylidene fluoride (PVDF) membranes (Millipore, Bedford, MA, USA) were blocked with 5% skimmed milk and 0.1% Tween-20 in phosphate-buffered saline and incubated with monoclonal anti-HA HA-11 (1:3000; BioLegend, San Diego, CA, USA, MMS-101P), monoclonal anti-FLAG M2 (1:3000; Sigma, F3165), anti-ZNT2 (1:3000) 24 , anti-Myc 9E10 (1:3000, Santa Cruz Biotechnology, Santa Cruz, CA, USA, sc-40), and anti-α-tubulin 12G10 (1:5000, deposited to the Developmental Studies Hybridoma Bank (DSHB) by Frankel, J. and Nelsen, E.M.) antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that ZNT5-ZNT6 heterodimers and ZNT7 homodimers are indispensable for the activation of several zinc ectoenzymes, including TNAP and PLAP, by using genetically engineered chicken DT40 cells (24)(25)(26)(27). However, a fundamental question that has remained unanswered is whether this holds true for mammalian cells, including human cells.…”
Section: Conserved Tnap-activation Functions Of Znt5-znt6 Heterodimermentioning
confidence: 99%
“…One of these roles of ZNT proteins is their critical function of supplying zinc to numerous proteins, including several secretory, extracellularly membrane-bound or organelle-resident enzymes biosynthesized in the compartments (hereafter zinc ectoenzymes), for their activation (20,21). In this context, we have shown that vertebrate ZNT5-ZNT6 heterodimers and ZNT7 homodimers are required for the activation of alkaline phosphatases (ALPs), such as tissue nonspecific ALP (TNAP) (22) and placental ALP (PLAP) (23), and several other ectoenzymes by using genetically engineered chicken DT40 cell mutants (24)(25)(26)(27).…”
mentioning
confidence: 99%